ANALISIS KUALITAS BUTIR SOAL PILIHAN GANDA MATA PELAJARAN KIMIA PADA UJIAN AKHIR SEMESTER (UAS) KELAS XI MAN 2 KEPULAUAN MERANTI - Ulfah Zahiroh; Pangoloan Soleman Ritonga (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
This research aimed at knowing the quality of test item derived from its validity, reliability, difficulty level, discriminator power, and distractor effectiveness. Quantitative descriptive method was used in this research. Interview and documentation were the techniques of collecting the data. The data source used was in evensemester exam questions that were in the forms of multiple-choice, student answer sheet, and answer key. Anates 4.0.9 program was to analyze the quality of test items. The research findings of the analysis of multiple-choice test item quality on semester final exam of Chemistry subject at the eleventh grade of State Islamic Senior High School 2 Kepulauan Meranti showed that in the validity analysis there were 6 valid test items (17%) and 29 non validitems (83%); in the reliability analysis it was obtained the reliability score 0.955; in the difficulty level analysis there were 12 easy test items (34%), 17 medium items (49%), and 6 hard items (17%); in the discriminator power analysis there were 4 very good test items (11.5%), a good item (3%), 19 items (54%) that should be revised, and 11 items (31.5%) that should be eliminated; in the distractor effectiveness there 26 very good options (19%), 10 good options (7%), 25 poor options (18%), 55 bad options (39%), and 24 very bad options (17%). Therefore, it could be concluded that the quality of test items could be stated bad.